Rapid lateral-flow immunoassay for the quantum dot-based detection of puerarin - Qu, Huihua; Zhang, Yue; Qu, Baoping; Kong, Hui; Qin, Gaofeng; Liu, Shuchen; Cheng, Jinjun; Wang, Qingguo; Zhao, Yan (Biosensors & bioelectronics, 2016)
In this study, a rapid (within 10min) quantitative lateral-flow immunoassay using a quantum dots (QDs)-antibody probe was developed for the analysis of puerarin (PUE) in water and biological samples. The competitive immunoassay was based on anti-PUE monoclonal antibody conjugated with QDs (detection reagent). Secondary antibody was immobilized on one end of a nitrocellulose membrane (control line) and PUE-bovine serum albumin conjugate was immobilized on the other end (test line). In the quantitative experiment, the detection results were scanned using a membrane strip reader and a detection curve (regression equation: y=−0.11ln(x)+0.979, R2=0.9816) representing the averages of the scanned data was obtained. This curve was linear from 1 to 10μg/mL. The IC50 value was 75.58ng/mL and the qualitative detection limit of PUE was 5.8ng/mL. The recovery of PUE added to phosphate-buffered saline and biological samples was in the range of 97.38–116.56%. To our knowledge, this is the first report of the quantitative detection of a natural product by QDs-based immunochromatography, which represents a powerful tool for rapidly screening PUE in plant materials and other biological samples. •A lateral-flow immunoassay based on anti-puerarin monoclonal antibody conjugated with quantum dots (QDs) was prepared.•For the bright fluorescent emission of the QDs, puerarin in plant materials and biological samples can be detected more sensitively.•The quantitative immunoassay is rapid (within 10 min), and requires no expensive instrumentation or specialist training.